Wayang Purwa Gagrag Banyumasan dan Peran Wali - muh nurul huda; Kundharu Saddhono (IBDA` : Jurnal Kajian Islam dan Budaya, 2017)
This article discusses the differences of puppet styles and the role of Wali towards puppet performance. The Nine Wali used puppet performance as one of their media to diffuse Islam. In addition to entertainment, puppet was functioned as guidance and rules for human life. To eliminate its syirik aspects, the Wali changed its substantial form of the puppets in order not to look like human being. This descriptive qualitative research studied the differences between purwa gagrag Banyumasan puppet and the role of Wali. This research found that there are some differences in names, forms, characters, and equipment in purwa gagrag Banyumasan puppet and the puppet innovated by the Wali. Meanwhile, the role of Wali existed on the changes of form and meaning of the puppets.